Автоматизированная система управления процессом сжигания топлива с переменной теплотворной способностью для нефтеперерабатывающей промышленности - Добровольская, Т.С.; Ложечников, В.Ф. (Проблемы управления и информатики, 2016)
Наведено синтезовану автоматизовану систему керування спалюванням несертифікованого палива у барабанних котлах, що працюють на загальний паропровід. Теплове навантаження між групою котлів розподілялось за оптимальним алгоритмом, в основі визначення якого є такі показники: ймовірність безвідмовної роботи обладнання та ефективність використання енергоресурсів. Наведено результати моделювання. A method of solving the optimization problem of the urban district heating is presented. Control is carried out on the basis of such elements as: the reliability and efficiency of the used equipment, and the cost of energy. The automated control system of the burning noncertified fuel in the drum boilers that work at the common steam line is synthesized. The heat load is distributed among a group of boilers according to the optimal algorithm. The results of numerical modeling are presented.